The Subjectivity of Forced-migrant in Poems of and by Refugees - Nurhadianty Rahayu (Journal of Language and Literature, 2020)
Refugeesperilous experiences force them to flee home for safety. Their arrival from home country tothehost country is not only often reduced to beastatistical number in factual reports but also seen as threats to national well-being. The study aims to provide the argument that poems provide a symbol of resistance towards refugeesgiven fate,and offer a platform for them to create their authentic version of knowledge.Poems are chosen to be analyzed in this study as they can mediate the refugeesunique experiences and their struggle to cope with the changing condition. The study argues that poemsof and by refugees can serve as strategic means of preserving memories that connect them with their past,which shape their present andconstructan alternative subjectivity against objectification and stereotypes pinned to them. Poemsanalyzed in this researchareHomebyWarsanShire,The IcebreakerbyYovankaPaquetePerdigao,andEmpathyby A.E. Stallings. Those excerpts areinterpretedthrough Feminist Refugee Epistemology (FRE),which according to Espiritu (2018),reveals the hidden political forces within the site of intimate domestic interaction in each refugees unique experiences and queer sociality.The study concluded that poemsof and by refugees couldfacilitate the forced-migrantsaspiration and create alternativeknowledgeas opposedto their common objectification in mass-media reports.